2016
DOI: 10.5530/ijopp.9.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceutical Waste Management An Overview

Abstract: Introduction: Medication disposal is an alarming issue today and gaining more and more awareness from the healthcare professionals as well as consumers. Pharmacists have the potential to be on the forefront of this movement as a healthcare professionals and pharmacists are in an admirable position to educate patients about safe drug disposal. Proper patient counselling on safe medication disposal can make a significant difference to public health and the environment. The knowledge on method of disposal of unus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 15 publications
(16 reference statements)
0
25
1
1
Order By: Relevance
“…Dietary supplements, for example, also contain heavy metals such as iron, zinc, manganese, selenium, and molybdenum which do not incinerate easily. Ideally, the burning of pharmaceutical waste should be precisely controlled, otherwise the remains from the burning sites still have the tendency to be discharged into the ecosystem where they may cause significant damage [79].…”
Section: Local Waste Management Strategiesmentioning
confidence: 99%
“…Dietary supplements, for example, also contain heavy metals such as iron, zinc, manganese, selenium, and molybdenum which do not incinerate easily. Ideally, the burning of pharmaceutical waste should be precisely controlled, otherwise the remains from the burning sites still have the tendency to be discharged into the ecosystem where they may cause significant damage [79].…”
Section: Local Waste Management Strategiesmentioning
confidence: 99%
“…Synthetic methods and characterization of these derivatives were reported in published research papers [14][15][16][17][18]. Bar graphs are plotted to explain % zone of inhibition and minimun zone of inhinbition to discuss the activity of compound against selected bacteria shown as below:…”
Section: Resultsmentioning
confidence: 99%
“…17,20 According to standard guidelines also small quantity liquid medications should be diluted with water and drained. 2 Drugs or their metabolites also find their path to enter the food chain through this route. 21 22 Medications Return Program or Take-back programs in Canada and Meds Disposal in Europe.…”
Section: Discussionmentioning
confidence: 99%
“…Proper waste management strategy is needed to ensure health and environmental safety. 2 From the questionnaire it was observed that the knowledge of medical personnel and student about ecopharmacology and problems associated with it was good. Attitude of medical personnel and students was also very empathetic, but this is not transforming into practices.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation